Autonoma symtom - diagnosövergripande hälsostörning - Nyström, Curt; Nyström, Orvar (Socialmedicinsk tidskrift, 2009)
Personer med långdraget förlopp i sin sjukdom tillsammans med begränsad arbetsförmåga aktualiseras för en försäkringsmedicinsk utredning. 1534 konsekutivt utredda personer har i denna studie besvarat Stress and Crisis Inventory -93, SCI-93, som kartlägger autonoma symtom och krisreaktion. Kartläggningen dokumenterade hos de utredda personerna närvaron av autonoma symtom i anmärkningsvärd omfattning. Denna manifestation av diagnosövergripande autonoma symtom har inte uppmärksammats och medicinskt värderats i tidigare genomförda utredningar. Traditional medical evaluation has been performed in 1534 disabled patients with limited working capacity. However, the limitation was not possible to explain as a reasonable effect of identified medical syndromes or diseases. Therefore, the patients were referred to the National Social Insurance Board Hospital in Tranås for further examinations. These included consecutively charting of autonomous symptoms and crisis processes with the Stress and Crisis Inventory –93. It is a self-questionnaire based on crisis models. The results indicated a significant presence of autonomous symptoms not identified in former examinations. Autonomous symptoms was significantly more pronounced in the patient group (n=1534) compared to a healthy reference group (n=100). The presence of significant autonomous symptoms together with former diagnoses can reliably be measured.